1967
DOI: 10.3758/bf03331612
|View full text |Cite
|
Sign up to set email alerts
|

Food-based timing behavior sharpened by the selective punishment of short interresponse times

Abstract: Food-based timing behavior sharpened by the selective punishment of short interresponse times I Following training on a DRL schedule three rats were punished for short interresponse times and a limited hold applied to the period of opportunity for food reinforcement. As a result the interresponse time distributions peaked sharply at the interval of reinforcement, and in one rat this time discrimination was shown to be strongly dependent upon punishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…These very short IRTs or response bursts were maintained even though they were infrequently reinforced. In the study of reinforcement, a variety of operations have also been shown to maintain a high relative frequency of very short IRTs in the absence of reinforcement for those IRTs (e.g., Anger, 1956;Blough, 1963Blough, , 1966Bruner, 1967 , 1964a, 1966Staddon, 1965 Blough (1966) suggested that these very short IRTs were produced by a change in key-peck topography coinciding with certain manipulations. That is, a change in response topography was thought to be responsible for the recording of double key pecks as two separate responses, or one very short IRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These very short IRTs or response bursts were maintained even though they were infrequently reinforced. In the study of reinforcement, a variety of operations have also been shown to maintain a high relative frequency of very short IRTs in the absence of reinforcement for those IRTs (e.g., Anger, 1956;Blough, 1963Blough, , 1966Bruner, 1967 , 1964a, 1966Staddon, 1965 Blough (1966) suggested that these very short IRTs were produced by a change in key-peck topography coinciding with certain manipulations. That is, a change in response topography was thought to be responsible for the recording of double key pecks as two separate responses, or one very short IRT.…”
Section: Discussionmentioning
confidence: 99%
“…In other research areas, interresponse time (IRT) measures have proven useful for such fine-grained analyses. Previous studies collecting IRT distributions in the study of punishment (Bruner, 1967;Holz, Azrin, & Ulrich, 1963;Malott & Cumming, 1964b) have not addressed the question of within-session punishing and facilitative effects of shock. The present study used an IRT analysis in the hope of uncovering systematic changes in the temporal distribution of responding which could be used to assess both response rate increases and decreases during intermittent punishment.…”
mentioning
confidence: 99%
“…Punishment of responses emitted prior to the DRL schedule has been a feature in DRL tasks for pigeons (Holz et al, 1963), monkeys (Galbicka and Branch, 1981), rats (Bruner. 1967), and even humans (Ç avdaro glu et al, 2014).…”
Section: Rats Can Learn and Perform Drl Responses For Reward Accompanied By Low-intensity Shockmentioning
confidence: 99%